ANALISA PENERAPAN MANAJEMEN WAKTU MENGGUNAKAN METODE CPM DAN PERT PADA PROYEK PEMBANGUNAN DAN REHABILITASI IFTK LEDALERO KABUPATEN SIKKA - Hironimus Lako Wea; Oktavianus Jori; Dedi Imanuel Pau (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2024)
Scheduling in projects involves determining the timeframe for project activities, including raw materials, labor, and time required for each task. Commonly used approaches include the Critical Path Method (CPM) and Project Evaluation Review Technique (PERT) to enhance Project planning and control quality. In utilizing the Critical Path Method (CPM) and Project Evaluation Review Technique (PERT) in the IFTK Ledalero Development and Rehabilitation Project, the process involves detailing the plan and sequence of work activities, calculating normal time (m), determining optimistic time (a), and pessimistic time (b) for each task. Additionally, Microsoft Excel 2007 application is utilized for data input, which includes time required for each task, labor requirements, labor wages, task sequences, and interdepencies. The critical path planning for the IFTK Ledalero Development and Rehabilitation Project identifies activities with a TF (Total Float) value of 0, resulting in a Project duration of 200 days. The acceleration efforts reduce the duration to 196 days with a 99.88% probability.